Study of the Corrosion Effect of High Voltage Alternating Networks on Nearby Metal Pipes - زهيرة محمد; حسام الدين علاء الدين (Latakia University Journal -Engineering Sciences Series, 2021)
In the 1980s, a new corrosion phenomenon emerged that is added to the known corrosion phenomena, resulting from the induced tensions in the pipes. This phenomenon is a result of the changing magnetic field resulting from the passage of an alternating current in the networks of high voltage when the pipeline path is adjacent to these networks. Studies have shown that the buried metal pipes Soil is greatly affected by high-voltage power transmission networks, where rust and corrosion are increased. This effect increases dramatically with the increase of the adjacent distance and the distance between the two networks, especially with parallel positioning on same side. Therefore, coating buried tubes , insulating layer and passing a continuous cathode protection current in them, previously known as cathodic protection, does not protect these tubes from corrosion and rust. This research aims to clarify the corrosion mechanism resulted from the alternating voltage induced in metal pipes buried in the ground, and to propose appropriate solutions according to what is listed in international standards. In addition, it seeks to study the relationship between alternating current density and cathode protection current density, to determine some limit values ​​of the voltage and the distance between the pipes and the electrical network and to study the effect of the specific resistance of the soil in which the tube is buried. During the stage of rebuilding the electricity and oil sectors, these networks can contiguous with each other, and many problems can be eliminated when the paths of these networks are properly studied before implementing them. When one of the two networks is implemented, and the other is under study, some measures can be taken according to what is mentioned. This study lead to reduction of cross-effect.